BEBERAPA PERMASALAHAN DALAM PENGANGGARAN MODAL - Widodo, Sri (Modus Journals, 2013)
In capital budgeting processes, there are some crucial problem related to infation and the criteria in making the decision. Among the two discounting methods, analysts may use NPV or IRR. If NPV is used in making capital investment decision, some still doubt that project having zero NPV is still a good project. In this paper we try to explore how important infation factor to be considered in capital badgeting. The fnancial professional literatures dealing with investment decisions, state in general that the net present value shows objective picture for the decision maker. The net present value shows the amount of wealth growth that have been accumulated by the investment during the life time of the project, but the investment’s internal rate of return informs the decision maker that how works the real yield of long capital investment. The NPV method is theoritically superior to the IRR method in dealing with mutually exclusive project. The Project having zero NPV is considered to be proftable. In general terms, a sound capital investment will earn its original investment and cover the cost of capital invested. In the countres with high rate of infation, the efect on capital investment can be dramatic, so that cash fow adjustment is very critical.Keywords : capital budgeting